Estimating intertemporal elasticity of substitution in a sticky price model - Juha Kilponen; Jouko Vilmunen; Oskari Vähämaa (Bank of Finland, 2013)
Cancellation of income and substitution effect implied by King-Plosser-Rebelo (1988) preferences breaks tight coefficient restriction between the slope of the Phillips curve and the elasticity of consumption with respect to real interest rate in a sticky price macro model. This facilitates the estimation of intertemporal elasticity of substitution using full information Bayesian Maximum Likelihood techniques within a structural model. The US data from the period 1984 - 2007 supports low intertemporal elasticity of substitution and strongly rejects a logarithmic and an additively separable utility specification commonly applied in the New Keynesian literature.
URN:NBN:fi:bof-20140807270
Keywords: E32; E52; E21; 330; Monetary policy; Bayesian estimation; Non-separable utility